Effects of land use change on ecosystem services value in West Jilin since the reform and opening of China - Fei, Li; Shuwen, Zhang; Jiuchun, Yang; Liping, Chang; Haijuan, Yang; Kun, Bu (Ecosystem services, 2018)
•Revised ESV calculation method based on biophysical and socioeconomic factor.•Spatially and quantitatively explored the impact of land use change on the ESV.•Provided a reference for an in-depth understanding of China's ecological change. Land resources were the foundation of human survival and development. The change of land use altered the pattern of vegetation and landscape, caused the change of ecosystem structure and function and changed the value of regional ecosystem services. This study spatially and quantitatively explored the impact of land use change on the ecosystem service value in West Jilin since the reform and opening of China. The results showed that the main characteristic of land use change in West Jilin was area reduction in grassland and marsh and area increase in arable land and alkali-land. However, land use change in Period I (1976–2000) got a faster rate than in Period II (2000–2013). Land use change resulted in the ESV in West Jilin decreased by 1334 million yuan since the reform and opening up of China, with an annual loss of 39.2 million yuan in Period I and 30.2 million yuan in Period II. The conversion of marsh to other types land use was the primary land use reason for the decrease in ESV. Alkali-land expanded quickly in Period I, however, the trend of salinization turned to be curbed and the area of alkali-land began to decrease after 2000, which increased the ESV by about 234 million yuan. Due to the concern of local government and relevant scientific research departments, the ecological and environmental deterioration were meliorated and the decrease rate of ecosystem services value also slowed down. Excitingly, ESV even increased in some areas on account of land use was becoming more rational.